Tumor Development in p53 Knockout Mice: A Review of Mice Deficient for p53 - Satyajit Patra (Journal of Proteomics and Genomics Research, 2018)
This review summarizes tumor development in p53‑deficient mouse models, discussing tissue specificity, cooperating pathways, and insights into human cancer biology.
Keywords: p53